Karakteristik Perseroan Perorangan Sebagai Perseroan Yang Memenuhi Kriteria Untuk Usaha Mikro Dan Kecil - Amelia Sri Kusuma Dewi (Fakultas Hukum Universitas Islam Malang, 2022)
One of the obstacles for micro and small businesses to develop is the low quality of organizational operations. The Employment Creation Act selects the legal entity form of an individual company in order to empower micro and small businesses. Based on the Employment Act, companies that meet the criteria for micro and small businesses can be established by one person, whereas so far a legal entity has been established based on an agreement of at least two shareholders. The author chooses the formulation of the problem regarding the fulfillment of an individual company as a company that meets the criteria for micro and small businesses against the legal principles regarding a PT legal entity, so when viewed from the basic norms of establishment, organs, capital, and dissolution. By using a legal approach, it can be ascertained that companies that meet the criteria for micro and small businesses, judging from the basic norms of establishment, organs, capital, and dissolution, do not meet the legal principles regarding the legal entity PT.